2022
DOI: 10.2147/ijwh.s341603
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on the Quality of Life in Women with Endometrioma

Abstract: Purpose:To evaluate the quality of life (QoL) of women with endometrioma and explore the associated factors. Patients and Methods: A cross-sectional study was conducted between August 2020 and March 2021. A total of 99 women diagnosed with ovarian endometrioma with at least one endometriosis-associated symptom completed the Endometriosis Health Profile 30 (EHP-30) questionnaire for their QoL score before treatment for ovarian endometrioma. The questionnaire comprises a central questionnaire (30 items) and a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The HRQoL of patients with endometriosis was negatively correlated with anxiety and depression ( 19 , 40 , 43 , 46 ). Facchin et al ( 15 ) reported a strong association between sleep disturbances and poorer psychological health and quality of life in women with endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…The HRQoL of patients with endometriosis was negatively correlated with anxiety and depression ( 19 , 40 , 43 , 46 ). Facchin et al ( 15 ) reported a strong association between sleep disturbances and poorer psychological health and quality of life in women with endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…Ovarian chocolate-like cysts or endometriomas are a major pathological manifestation of endometriosis, occurring in approximately 17–44% of women diagnosed with endometriosis [ 1 ]. While ovarian endometriomas may adversely affect quality of life and work performance, to the best of our knowledge, the association between cyst size and the pain in women with ovarian endometriomas has not been elucidated [ 2 ]. Therefore, in this retrospective study, we assessed the association between clinical epidemiological background and ovarian endometriomas, focusing on the association among age, ovarian endometrioma size, and pain, using data from patients enrolled in six prospective clinical studies [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cardinal symptoms of endometriosis are primary or secondary dysmenorrhea, chronic recurrent abdominal pain, pain during sexual intercourse, abdominal distension, dysuria and infertility [15][16][17] . Various studies have shown that endometriosis reduces the quality of life of affected women [1,18,19] . In addition to having physical, mental and social consequences for affected women at the individual level [12], endometriosis is estimated to have signi cant economic impacts on society as a whole [20][21][22], due mainly to increased healthcare utilization and reduced work productivity [21,23,24] .…”
Section: Introductionmentioning
confidence: 99%